Long term context for bushfires in inhabited and uninhabited landscapes: A Holocene record from Kangaroo Island (Karti/Karta), South Australia - Lucinda Cameron Duxbury; Haidee Cadd; Wallace Boone Law; Alexander Francke; Stefan Löhr; Lluka Yohanni Johns-Mead; Philip Anthony Hall; Linda Armbrecht; Jonathan James Tyler (Global and Planetary Change, 2026)

Corrigendum to “Estimating irrigation consumptive use for the conterminous United States: coupling satellite-sourced estimates of actual evapotranspiration with a national hydrologic model” [J. Hydrol. 662 (2025) 133909] - Donald J. Martin; Richard G. Niswonger; R.Steve Regan; Justin L. Huntington; Thomas Ott; Charles Morton; Gabriel B. Senay; MacKenzie Friedrichs; Forrest S. Melton; Jonathan Haynes; Wesley Henson; Amy Read; et al. (Journal of Hydrology, 2026)

Impurity incorporation and strain dynamics in calcite crystal growth: in situ analysis and multiscale chemical-strain mapping - Si Athena Chen; Sabine M. Neumayer; Michael J. Zachman; Anton V. Ievlev; Jonathan D. Poplawsky; Tyler L. Spano; Peter J. Eng; Andrew G. Stack; Juliane Weber (Geochimica et Cosmochimica Acta, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Clarifying space use concepts in ecology: Range vs. occurrence distributions - Jesse M. Alston; Christen H. Fleming; Michael J. Noonan; Marlee A. Tucker; Inês Silva; Cody Folta; Thomas S. B. Akre; Abdullahi H. Ali; Jerrold L. Belant; Dean Beyer; Niels Blaum; Katrin Böhning‐Gaese; et al. (Ecology, 2026)
Quantifying animal movements is necessary for answering a wide array of research questions in ecology and conservation biology. Consequently, ecologists have made considerable efforts to identify the best way to estimate an animal's home range, and many methods of estimating home ranges have arisen over the past half a century. Most of these methods fall into two distinct categories of estimators that have only recently been described in statistical detail: those that measure range distributions (methods such as kernel density estimation that quantify the long‐run behavior of a movement process that features restricted space use) and those that measure occurrence distributions (methods such as Brownian bridge movement models and the Correlated Random Walk Library that quantify uncertainty in an animal movement path during a specific period of observation). In this paper, we use theory, simulations, and empirical analysis to demonstrate the importance of appropriately using these two categories of distributions and their estimators. Conflating range and occurrence distributions can have serious consequences for ecological inference and conservation practice. For example, in most situations, home ranges estimated using estimators of occurrence distributions are too small, and this problem is exacerbated by ongoing improvements in tracking technology that enable more frequent and more accurate data on animal movements. We encourage researchers to use estimators of range distributions to quantify home ranges and estimators of occurrence distributions to answer other questions in movement ecology, such as when and where an animal crossed a linear feature, visited a location of interest, or interacted with other animals.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Tracking millennial-scale climate variability during the last glacial period using aquatic productivity indicators from Lake Suigetsu, Japan - Vanessa Nowinski; Alexander Francke; John Tibby; Takeshi Nakagawa; Tony Hall; Ikuko Kitaba; Jonathan Tyler (Quaternary Science Reviews, 2025)

Estimating irrigation consumptive use for the conterminous United States: coupling satellite-sourced estimates of actual evapotranspiration with a national hydrologic model - Donald J. Martin; Richard G. Niswonger; R. Steve Regan; Justin L. Huntington; Thomas Ott; Charles Morton; Gabriel B. Senay; MacKenzie Friedrichs; Forrest S. Melton; Jonathan Haynes; Wesley Henson; Amy Read; et al. (Journal of Hydrology, 2025)

Landscape-level canopy heterogeneity improves avian conservation value in Appalachian forests: Implications for dynamic forest restoration - Cameron J. Fiss; Jonathan B. Cohen; Tyler J. Hodges; Dakotah R. Shaffer; Darin J. McNeil; Jeffery L. Larkin (Forest Ecology and Management, 2025)

Orbital-scale East Asian monsoon variability since the last interglacial inferred from the sediments of Lake Suigetsu, Japan - Alexander Francke; Jonathan J. Tyler; Richard Staff; Danielle McLean; Vanessa Nowinski; Megumi Saito-Kato; John Tibby; Minoru Ikehara; Yusuke Yokoyama; Katsuya Gotanda; Tsuyoshi Haraguchi; Takeshi Nakagawa (Quaternary Science Reviews, 2025)

Mid‐Holocene drying of K'gari lakes (subtropical eastern Australia) necessitates re‐evaluation of the El Niño–Southern Oscillation climate links and future drying risk - John Tibby; Haidee Cadd; Matthew Harris; Jonathan C. Marshall; Jonathan Tyler; Cameron Barr; Francesca McInerney; Patrick Moss; Claire Murphy; Patricia S. Gadd; Geraldine E. Jacobsen; Mathew Raven; et al. (Journal of Quaternary Science, 2025)
The Holocene history of Australia's climate is surprisingly poorly understood. This is, in part, because of the relatively weak forcing of Holocene climate versus that of the late Pleistocene. However, it is commonly suggested that eastern Australia dried during the mid‐ to late‐Holocene and that this was in response to increased activity in the El Niño–Southern Oscillation (ENSO), in particular, the intensification of the El Niño phase of ENSO. While this has been inferred from numerous locations, data from K'gari (a subtropical sand island adjacent to the east coast) was amongst the first used to develop this hypothesis and features heavily in the discussion of ENSO intensification. This study examines published and new data from three ≥4.5 m deep K'gari lakes that demonstrate a strong drying event during the middle Holocene (from 7640 to 5600 cal a BP), followed by a wetter late Holocene climate. This contrasts somewhat with previous arguments about K'gari's history that suggest a late Holocene drying. In turn, this indicates a need to re‐evaluate the notion that ENSO intensification drove late‐Holocene drying in the region. It also indicates that even large, deep lakes on K'gari, which are iconic landmarks with substantial cultural, ecological and economic values, are vulnerable to drying.

A 2000-year record of hydroclimate variability inferred from oxygen isotopes in lake sediments on Kangaroo Island (Karti/Karta), South Australia - Mahfuzur Rahman; Lucinda Duxbury; Haidee Cadd; Robert Klaebe; Geraldine Jacobsen; John Tibby; Jonathan Tyler (Quaternary Science Reviews, 2025)

Developing robust lake sediment chronologies using 210Pb, Pu and radiocarbon dating of pollen concentrates and macrofossil: A case study from Lake Surprise, Victoria, Australia - Asika Dharmarathna; Haidee Cadd; Cameron Barr; Alexander Francke; Quan Hua; David Child; Michael Hotchkis; Atun Zawadzki; Patricia Gadd; Chris Turney; Christopher E. Marjo; John Tibby; et al. (Quaternary Geochronology, 2025)

Reduction of postharvest fungal spoilage of tomato fruit using bacterial antagonists - Hailey R. Graham; Jonathan Ononiwu; Sydney Massine; Jason Lafontaine; Tyler J. Avis (Journal of Plant Pathology, 2025)

Temperature‐dependent growth and activity in a globally distributed nitrogen‐fixing haptophyte - Esther Wing Kwan Mak; Kendra A. Turk‐Kubo; Anna V. Voznyuk; Mary R. Gradoville; Tyler Coale; Kyoko Hagino; Jonathan P. Zehr (Limnology and Oceanography, 2025)
Dinitrogen (N 2 )‐fixing microorganisms play a crucial role in supplying nitrogen (N) to the oceans by converting atmospheric N 2 into bioavailable N. N 2 fixation was thought to be limited to warm oligotrophic ocean waters, but the association between the N 2 ‐fixing UCYN‐A cyanobacterium and specific haptophytes, including Braarudosphaera bigelowii and relatives, has been found in diverse ocean environments, including warm subtropical gyres, temperate coastal systems, and cold polar waters. UCYN‐A2, previously known as the symbiont of B. bigelowii , and now considered an early‐stage organelle that exchanges fixed nitrogen for fixed carbon, has only recently been cultured. This study investigated the growth and activity of B. bigelowii in response to a range of temperatures to better understand its global distribution and ecology. Incubation experiments were conducted with B. bigelowii to determine growth rates, carbon (C) and N 2 fixation rates, and cell sizes across a temperature range of 6–26°C. Growth rates were highest between 10°C and 22°C and lowest at 6°C and 26°C. Significant positive correlations were found between cell count‐based growth rates, C‐specific and N‐specific growth rates. Braarudosphaera bigelowii cell size increased at low temperatures. The growth and metabolic activity detected across a wide range of temperatures help to explain the wide geographic distribution of B. bigelowii . This study presents the first growth and activity measurements under a range of temperatures from B. bigelowii , providing vital information needed to understand the unique ecology of this organism and to parameterize its activity in ecosystem models.

Australian subtropical vegetation and wetland response to fire, climate and nutrient availability during the Holocene - Haidee Cadd; Michela Mariani; John Tibby; Jonathan Tyler; Cameron Barr; Melanie J. Leng; Patrick Moss; Richard Lewis; Tim Cohen; Sam Marx; Glenn B. McGregor; Jonathan C. Marshall; et al. (Journal of Quaternary Science, 2025)
The iconic sand dune systems of Minjerribah (North Stradbroke Island), in southeastern Queensland, Australia, host numerous lakes and swamps containing organic‐rich sediment deposits that record changes in climate, fire and surrounding vegetation. Palaeoenvironmental reconstructions from individual locations can provide insights into changes in the environment, but determining the regional extent of these changes is seldom possible from a single site. Multi‐site compilations help elucidate the geographical nature of environmental changes and determine if they are driven by local or regional forces. Here, a synthesis of palynological records from six Minjerribah wetlands using a muti‐tiered Monte Carlo empirical orthogonal function (EOF) analysis allows island‐wide patterns of vegetation change to be identified. Coherent changes in vegetation were recorded, with first‐order changes (EOF1) indicating a long‐term shift in vegetation composition from closed forests towards woodland and heath vegetation. A compilation of macroscopic and microscopic charcoal from the same sites shares coherent patterns of change with a rainfall record from the island, suggesting that regional fire occurrence between 7000 and 2000 cal a bp was driven primarily by long‐term variations in rainfall and its influence on biomass. Comparison with fire activity, rainfall, sedimentary carbon, nitrogen and dust records from Minjerribah suggests that regional vegetation changes occur primarily in response to long‐term changes in nutrients and increasing rainfall variability. This analysis highlights the multi‐millennial connection between vegetation composition, climate, nutrients and fire occurrence across the Holocene in subtropical environments.

Determination of the zebrafish embryo developmental toxicity assessment (ZEDTA) as an alternative non-mammalian approach for the safety assessment of agrochemicals - Jonathan S. Ball; Anna Tochwin; Matthew J. Winter; Maciej Trznadel; Richard Currie; Kathryn Wolton; Julian M. French; Malcolm J. Hetheridge; Charles R. Tyler (Reproductive Toxicology, 2025)

Regional Processes Mediate Ecological Selection and the Distribution of Plant Diversity Across Scales - Christopher P. Catano; Jonathan Bauer; Tyler Bassett; Eric Behrens; Lars A. Brudvig (Ecology Letters, 2025)
Community ecology remains focused on interactions at small scales, which limits causal understanding of how regional and local processes interact to mediate biodiversity changes. We hypothesise that species pool size and immigration are two regional processes altering the balance between local niche selection and drift that cause variation in plant diversity. We manipulated the richness and number of seeds sown (species pool size and immigration respectively) into 12 grasslands across a landscape soil moisture gradient. Greater immigration and smaller species pools increased the variation in plant composition explained by soil moisture gradients but resulted in greater erosion of plant α ‐diversity and spatial β ‐diversity over time. Our results suggest that regional constraints on colonisation make community assembly more variable but help maintain species diversity by limiting biotic homogenisation. This study provides large‐scale experimental evidence on how regional contexts can alter the relative importance of fundamental processes shaping biodiversity change across scales.

Temperature and hydrological change in central Australia through the last glacial cycle: Insights from clumped isotope analysis of lacustrine molluscs - Fletcher C. Nixon; Jonathan J. Tyler; Robert M. Klaebe; Stacey C. Priestley; Quan Hua; Lee J. Arnold; Tim J. Cohen (Quaternary Science Reviews, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Exposure effects of synthetic glucocorticoid drugs on skeletal developmental and immune cell function in zebrafish - Charles M. Hamilton; Matthew J. Winter; Jonathan S. Ball; Maciej Trznadel; Luigi Margiotta-Casaluci; Stewart F. Owen; Charles R. Tyler (Science of The Total Environment, 2024)

Elevated temperature exacerbates pharmaceutical-induced oxidative stress in zebrafish (Danio rerio) larvae - Rebekah Boreham; Jonathan S. Ball; Malcolm Hetheridge; Stewart Owen; Maciej Trznadel; Charles R. Tyler (Science of The Total Environment, 2024)

Piloting wastewater-based surveillance of norovirus in England - David I. Walker; Jessica Witt; Wayne Rostant; Robert Burton; Vicki Davison; Jackie Ditchburn; Nicholas Evens; Reg Godwin; Jane Heywood; James A. Lowther; Nancy Peters; Jonathan Porter; et al. (Water Research, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

fNIRS is capable of distinguishing laterality of lower body contractions - Rob J. MacLennan; Jesus A. Hernandez-Sarabia; Shawn M. Reese; JoCarol E. Shields; Claire M. Smith; Katharina Stute; Jordyn Collyar; Alex A. Olmos; Tyler L. Danielson; Demi L. MacLennan; Jason I. Pagan; Ryan M. Girts; et al. (Experimental Brain Research, 2024)

A model for community-driven development of best practices: the Ocean Observatories Initiative Biogeochemical Sensor Data Best Practices and User Guide - Hilary I. Palevsky; Sophie Clayton; Heather Benway; Mairead Maheigan; Dariia Atamanchuk; Roman Battisti; Jennifer Batryn; Annie Bourbonnais; Ellen M. Briggs; Filipa Carvalho; Alison P. Chase; Rachel Eveleth; et al. (Frontiers in Marine Science, 2024)
The field of oceanography is transitioning from data-poor to data-rich, thanks in part to increased deployment of in-situ platforms and sensors, such as those that instrument the US-funded Ocean Observatories Initiative (OOI). However, generating science-ready data products from these sensors, particularly those making biogeochemical measurements, often requires extensive end-user calibration and validation procedures, which can present a significant barrier. Openly available community-developed and -vetted Best Practices contribute to overcoming such barriers, but collaboratively developing user-friendly Best Practices can be challenging. Here we describe the process undertaken by the NSF-funded OOI Biogeochemical Sensor Data Working Group to develop Best Practices for creating science-ready biogeochemical data products from OOI data, culminating in the publication of the GOOS-endorsed OOI Biogeochemical Sensor Data Best Practices and User Guide. For Best Practices related to ocean observatories, engaging observatory staff is crucial, but having a “user-defined” process ensures the final product addresses user needs. Our process prioritized bringing together a diverse team and creating an inclusive environment where all participants could effectively contribute. Incorporating the perspectives of a wide range of experts and prospective end users through an iterative review process that included “Beta Testers’’ enabled us to produce a final product that combines technical information with a user-friendly structure that illustrates data analysis pipelines via flowcharts and worked examples accompanied by pseudo-code. Our process and its impact on improving the accessibility and utility of the end product provides a roadmap for other groups undertaking similar community-driven activities to develop and disseminate new Ocean Best Practices.

Who’s a pretty bird? Predicting the traded abundance of bird species in Australian online pet trade - Katherine G. W. Hill; Oliver C. Stringham; Stephanie Moncayo; Adam Toomes; Jonathan J. Tyler; Phillip Cassey; Steven Delean (Biological Invasions, 2024)

Holocene climate and catchment change inferred from the geochemistry of Lashmars Lagoon, Kangaroo Island (Karti/Karta), southern Australia - Lucinda Cameron Duxbury; Lluka Yohanni Johns-Mead; Haidee Cadd; Alexander Francke; Stefan C. Löhr; Wallace Boone Law; Linda Armbrecht; Philip Anthony Hall; Atun Zawadzki; Geraldine E. Jacobsen; Patricia S. Gadd; David P. Child; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Mechanisms for generating elevated zircon δ18O in Archean crust: Insights from the Saglek-Hebron Complex, Canada - Emily E. Mixon; Ann M. Bauer; Jonathan O'Neil; Hanika Rizo; Tyler B. Blum; John W. Valley; Chloë E. Bonamici (Earth and Planetary Science Letters, 2023)

High‐resolution stable isotope profiles from shells of the land snail Placostylus reveal contrasting patterns between snails originating from New Zealand and New Caledonia - Mathieu Quenu; Emily J. Judd; Mary Morgan‐richards; Steven A. Trewick; Katherine Holt; Jonathan Tyler; Andrew M. Lorrey (Journal of Quaternary Science, 2023)
The stable oxygen (δ 18 O shell ) and carbon (δ 13 C shell ) isotope ratios retrieved from the carbonate shell of terrestrial gastropods can be used as an environmental proxy and are thought to reflect dietary composition and ambient climatic conditions (e.g. precipitation amount, humidity, temperature). Here, we generate high‐resolution isotopic profiles of nine modern land snails of the genus Placostylus , collected from two locations in New Caledonia and one location in New Zealand. We found that snails from New Zealand had, on average, higher δ 18 O shell values than their counterparts in New Caledonia, which surprisingly runs counter to the expected relationship based on the isotopic composition of rainwater between these two regions. Specimens from New Caledonia exhibit ephemeral decreases in their δ 18 O shell values, which could be linked to extreme precipitation events in this region, while snails from New Zealand have less variation in their δ 18 O shell values. Snails from New Zealand had, on average, slightly higher δ 13 C shell than their counterparts in New Caledonia, but a large difference in carbon isotopes was sometimes observed between snails collected at the same location. Most snails exhibit a temporal trend in their δ 13 C shell values, indicating potential shifts in diet through to maturity.

Predicting spatial distribution of stable isotopes in precipitation by classical geostatistical- and machine learning methods - Dániel Erdélyi; István Gábor Hatvani; Hyeongseon Jeon; Matthew Jones; Jonathan Tyler; Zoltán Kern (Journal of Hydrology, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

A computational method for rapid orthographic photography of lake sediment cores - Martin James Ankor; Jonathan James Tyler (Journal of Paleolimnology, 2022)
Photographs of sediment cores are an important dataset, often containing visual evidence for environmental change via sediment composition and structure. These photographs may be used to stratigraphically correlate adjacent cores or for automated image analysis, and can facilitate collaboration amongst researchers through sharing and annotation of the image files. Here we describe the use of computational photogrammetry (also known as Structure from Motion–Multi-View Stereo) to generate orthographic imagery of sediment cores. Computational photogrammetry is a rapid and economical technique, typically requiring only a few minutes for each metre of core, using consumer-grade digital camera equipment. The photogrammetric methodology corrects for topographic distortion caused by sediment surfaces that are not perfectly flat, and can also record features of the scene surrounding the core, such as notes, colour reference cards and measurement tapes or rulers. As the photogrammetric process also generates a three-dimensional reconstruction of the sediment core, spatial-based analysis can be used to identify damaged or non-representative sections of the core that are to be avoided during image analysis. Using an intermittently laminated sediment core from Lake Surprise, Australia, we tested 22 scenarios using control points in a variety of configurations, as well as calibrated and uncalibrated cameras, to identify techniques that can reconstruct the core accurately and generate orthophotos. Multiple techniques were able to achieve suitable accuracy. In particular, targets placed on the table alongside the core, combined with a calibrated camera, achieved high accuracy and enabled a simple, rapid, and repeatable method for generating high-quality sediment core images.

Genomic erosion in a demographically recovered bird species during conservation rescue - Hazel A. Jackson; Lawrence Percival‐Alwyn; Camilla Ryan; Mohammed F. Albeshr; Luca Venturi; Hernán E. Morales; Thomas C. Mathers; Jonathan Cocker; Samuel A. Speak; Gonzalo G. Accinelli; Tom Barker; Darren Heavens; et al. (Conservation Biology, 2022)
The pink pigeon ( Nesoenas mayeri ) is an endemic species of Mauritius that has made a remarkable recovery after a severe population bottleneck in the 1970s to early 1990s. Prior to this bottleneck, an ex situ population was established from which captive‐bred individuals were released into free‐living subpopulations to increase population size and genetic variation. This conservation rescue led to rapid population recovery to 400–480 individuals, and the species was twice downlisted on the International Union for the Conservation of Nature (IUCN) Red List. We analyzed the impacts of the bottleneck and genetic rescue on neutral genetic variation during and after population recovery (1993–2008) with restriction site‐associated sequencing, microsatellite analyses, and quantitative genetic analysis of studbook data of 1112 birds from zoos in Europe and the United States. We used computer simulations to study the predicted changes in genetic variation and population viability from the past into the future. Genetic variation declined rapidly, despite the population rebound, and the effective population size was approximately an order of magnitude smaller than census size. The species carried a high genetic load of circa 15 lethal equivalents for longevity. Our computer simulations predicted continued inbreeding will likely result in increased expression of deleterious mutations (i.e., a high realized load) and severe inbreeding depression. Without continued conservation actions, it is likely that the pink pigeon will go extinct in the wild within 100 years. Conservation rescue of the pink pigeon has been instrumental in the recovery of the free‐living population. However, further genetic rescue with captive‐bred birds from zoos is required to recover lost variation, reduce expression of harmful deleterious variation, and prevent extinction. The use of genomics and modeling data can inform IUCN assessments of the viability and extinction risk of species, and it helps in assessments of the conservation dependency of populations.

Investigating the palaeoenvironmental context of Late Pleistocene human dispersals into Southeast Asia: a review of stable isotope applications - Meghan S. McAllister; Mike W. Morley; Jonathan J. Tyler; Francesca A. McInerney; Alison J. Blyth (Archaeological and Anthropological Sciences, 2022)
We review palaeoenvironmental applications of stable isotope analysis to Late Pleistocene archaeological sites across Southeast Asia (SEA), a region critical to understanding the evolution of Homo sapiens and other co-existing Late Pleistocene (124–11.7 ka) hominins. Stable isotope techniques applied to archaeological deposits offer the potential to develop robust palaeoenvironmental reconstructions, to contextualise the occupational and non-occupational history of a site. By evaluating the published research in this field, we show that sediments, guano, tooth enamel, speleothem and biomolecular material such as leaf waxes have great potential to provide site-specific palaeoenvironmental records and local and catchment-scale landscape context to hominin dispersal in the region. However, stable isotope techniques used in these contexts are in their infancy in SEA, and the diagenetic controls associated with hot and humid environments that typify the region are not yet fully understood. Additionally, availability of sources of stable isotopes varies between sites. Nonetheless, even the limited research currently available shows that stable isotope analyses can aid in developing a better understanding of the role of the environment on the nature and timing of dispersals of our species eastwards into SEA and beyond.

Ecology and climate sensitivity of a groundwater-fed lake on subtropical North Stradbroke Island (Minjerribah), Queensland, Australia over the last 7500 years - Charles Maxson; John Tibby; Cameron Barr; Jonathan Tyler; Melanie Leng; Barry Lomax; Jonathan Marshall; Glenn McGregor; Cameron Schulz; Haidee Cadd; Geraldine Jacobsen (Journal of Paleolimnology, 2022)

Environmental Controls on the Geochemistry of a Short-Lived Bivalve in Southeastern Australian Estuaries - Briony K. Chamberlayne; Jonathan J. Tyler; Bronwyn M. Gillanders (Estuaries and Coasts, 2020)

Emerging risk governance for stratospheric aerosol injection as a climate management technology - Khara D. Grieger; Tyler Felgenhauer; Ortwin Renn; Jonathan Wiener; Mark Borsuk (Environment Systems and Decisions, 2019)

Normal modes and resonance in Ontario Lacus: a hydrocarbon lake of Titan - David Vincent; Jonathan Lambrechts; Özgür Karatekin; Tim Van Hoolst; Robert H. Tyler; Véronique Dehant; Eric Deleersnijder (Ocean Dynamics, 2019)

Development of a spreadsheet-based model for transient groundwater modelling - Martin J. Ankor; Jonathan J. Tyler (Hydrogeology Journal, 2019)

Defining a Safe Operating Space for inland recreational fisheries - Stephen R Carpenter; William A Brock; Gretchen J A Hansen; Jonathan F Hansen; Joseph M Hennessy; Daniel A Isermann; Eric J Pedersen; K Martin Perales; Andrew L Rypel; Greg G Sass; Tyler D Tunney; M Jake Vander Zanden (Fish and Fisheries, 2017)
The Safe Operating Space ( SOS ) of a recreational fishery is the multidimensional region defined by levels of harvest, angler effort, habitat, predation and other factors in which the fishery is sustainable into the future. SOS boundaries exhibit trade‐offs such that decreases in harvest can compensate to some degree for losses of habitat, increases in predation and increasing value of fishing time to anglers. Conversely, high levels of harvest can be sustained if habitat is intact, predation is low, and value of fishing effort is moderate. The SOS approach recognizes limits in several dimensions: at overly high levels of harvest, habitat loss, predation, or value of fishing effort, the stock falls to a low equilibrium biomass. Recreational fisheries managers can influence harvest and perhaps predation, but they must cope with trends that are beyond their control such as changes in climate, loss of aquatic habitat or social factors that affect the value of fishing effort for anglers. The SOS illustrates opportunities to manage harvest or predation to maintain quality fisheries in the presence of trends in climate, social preferences or other factors that are not manageable.

An acute session of roller massage prolongs voluntary torque development and diminishes evoked pain - Mark Tyler Cavanaugh; Alexander Döweling; James Douglas Young; Patrick John Quigley; Daniel David Hodgson; Joseph H. D. Whitten; Jonathan C. Reid; Saied Jalal Aboodarda; David G. Behm (European Journal of Applied Physiology, 2017)

Natural hazards in Australia: droughts - Anthony S. Kiem; Fiona Johnson; Seth Westra; Albert van Dijk; Jason P. Evans; Alison O’Donnell; Alexandra Rouillard; Cameron Barr; Jonathan Tyler; Mark Thyer; Doerte Jakob; Fitsum Woldemeskel; et al. (Climatic Change, 2016)

Carbon isotope discrimination in leaves of the broad‐leaved paperbark tree, Melaleuca quinquenervia , as a tool for quantifying past tropical and subtropical rainfall - John Tibby; Cameron Barr; Francesca A. McInerney; Andrew C. G. Henderson; Melanie J. Leng; Margaret Greenway; Jonathan C. Marshall; Glenn B. McGregor; Jonathan J. Tyler; Vivienne McNeil (Global Change Biology, 2016)
Quantitative reconstructions of terrestrial climate are highly sought after but rare, particularly in Australia. Carbon isotope discrimination in plant leaves (Δ leaf ) is an established indicator of past hydroclimate because the fractionation of carbon isotopes during photosynthesis is strongly influenced by water stress. Leaves of the evergreen tree Melaleuca quinquenervia have been recovered from the sediments of some perched lakes on North Stradbroke and Fraser Islands, south‐east Queensland, eastern Australia. Here, we examine the potential for using M. quinquenervia ∆ leaf as a tracer of past rainfall by analysing carbon isotope ratios ( δ 13 C) of modern leaves. We firstly assess Δ leaf variation at the leaf and stand scale and find no systematic pattern within leaves or between leaves due to their position on the tree. We then examine the relationships between climate and Δ leaf for a 11‐year time series of leaves collected in a litter tray. M. quinquenervia retains its leaves for 1–4 years; thus, cumulative average climate data are used. There is a significant relationship between annual mean ∆ leaf and mean annual rainfall of the hydrological year for 1–4 years (i.e. 365–1460 days) prior to leaf fall ( r 2 = 0.64, P = 0.003, n = 11). This relationship is marginally improved by accounting for the effect of p CO 2 on discrimination ( r 2 = 0.67, P = 0.002, n = 11). The correlation between rainfall and Δ leaf , and the natural distribution of Melaleuca quinquenervia around wetlands of eastern Australia, Papua New Guinea and New Caledonia offers significant potential to infer past rainfall on a wide range of spatial and temporal scales.

Spatial patterns in the oxygen isotope composition of daily rainfall in the British Isles - Jonathan J. Tyler; Matthew Jones; Carol Arrowsmith; Tim Allott; Melanie J. Leng (Climate Dynamics, 2016)

Caribbean mesophotic coral ecosystems are unlikely climate change refugia - Tyler B. Smith; Joanna Gyory; Marilyn E. Brandt; William J. Miller; Jonathan Jossart; Richard S. Nemeth (Global Change Biology, 2016)
Deeper coral reefs experience reduced temperatures and light and are often shielded from localized anthropogenic stressors such as pollution and fishing. The deep reef refugia hypothesis posits that light‐dependent stony coral species at deeper depths are buffered from thermal stress and will avoid bleaching‐related mass mortalities caused by increasing sea surface temperatures under climate change. This hypothesis has not been tested because data collection on deeper coral reefs is difficult. Here we show that deeper (mesophotic) reefs, 30–75 m depth, in the Caribbean are not refugia because they have lower bleaching threshold temperatures than shallow reefs. Over two thermal stress events, mesophotic reef bleaching was driven by a bleaching threshold that declines 0.26 °C every +10 m depth. Thus, the main premise of the deep reef refugia hypothesis that cooler environments are protective is incorrect; any increase in temperatures above the local mean warmest conditions can lead to thermal stress and bleaching. Thus, relatively cooler temperatures can no longer be considered a de facto refugium for corals and it is likely that many deeper coral reefs are as vulnerable to climate change as shallow water reefs.

A diatom‐inferred record of lake variability during the last 900 years in Lützow–Holm Bay, East Antarctica - Rachel C. Rudd; Jonathan J. Tyler; John Tibby; Yusuke Yokoyama; Ines Tavernier; Elie Verleyen; Manabu Fukui; Yoshinori Takano (Journal of Quaternary Science, 2016)
Decadal–centennial‐scale climate variability in coastal Antarctica remains poorly understood due to the limited number of highly resolved, well‐dated records. We present a 900‐year, decadal‐scale reconstruction based on sedimentary diatoms from Lake Abi in Lützow–Holm Bay, East Antarctica. Hydrological change is inferred from diatom ecological preferences in conjunction with an existing regional training set and implies that lake water specific conductivity, depth and nitrogen availability are the key drivers of diatom assemblage change. Lake Abi underwent a series of subtle environmental changes related to these environmental variables, possibly driven by changes in catchment snow melt and the duration of seasonal ice cover. Ordination is used to trace the major patterns of change in the diatom community, with notable shifts identified between 470 and 400 and at ∼350 cal a BP (where present = CE 1950). The frequency of environmental variability at Lake Abi is broadly consistent with a record of the Interdecadal Pacific Oscillation during the last millennium, but contrasts with the apparent climate stability elsewhere in eastern Antarctica. Further research is required to constrain the limnological and ecological responses of lakes in coastal Antarctica to obtain more rigorous palaeoclimate reconstructions from these sites of immense potential.

Acute bouts of upper and lower body static and dynamic stretching increase non-local joint range of motion - David George Behm; Tyler Cavanaugh; Patrick Quigley; Jonathan Christopher Reid; Priscyla Silva Monteiro Nardi; Paulo Henrique Marchetti (European Journal of Applied Physiology, 2016)

Burrow forms, growth rates and feeding rates of wood-boring Xylophagaidae bivalves revealed by micro-computed tomography - Diva J. Amon; Daniel Sykes; Farah Ahmed; Jonathan T. Copley; Kirsty M. Kemp; Paul A. Tyler; Craig M. Young; Adrian G. Glover (Frontiers in Marine Science, 2015)

A bioenergetic framework for the temperature dependence of trophic interactions - Benjamin Gilbert; Tyler D. Tunney; Kevin S. McCann; John P. DeLong; David A. Vasseur; Van Savage; Jonathan B. Shurin; Anthony I. Dell; Brandon T. Barton; Christopher D.G. Harley; Heather M. Kharouba; Pavel Kratina; et al. (Ecology Letters, 2014)
Changing temperature can substantially shift ecological communities by altering the strength and stability of trophic interactions. Because many ecological rates are constrained by temperature, new approaches are required to understand how simultaneous changes in multiple rates alter the relative performance of species and their trophic interactions. We develop an energetic approach to identify the relationship between biomass fluxes and standing biomass across trophic levels. Our approach links ecological rates and trophic dynamics to measure temperature‐dependent changes to the strength of trophic interactions and determine how these changes alter food web stability. It accomplishes this by using biomass as a common energetic currency and isolating three temperature‐dependent processes that are common to all consumer–resource interactions: biomass accumulation of the resource, resource consumption and consumer mortality. Using this framework, we clarify when and how temperature alters consumer to resource biomass ratios, equilibrium resilience, consumer variability, extinction risk and transient vs. equilibrium dynamics. Finally, we characterise key asymmetries in species responses to temperature that produce these distinct dynamic behaviours and identify when they are likely to emerge. Overall, our framework provides a mechanistic and more unified understanding of the temperature dependence of trophic dynamics in terms of ecological rates, biomass ratios and stability.

Goldilocks Meets Santa Rosalia: An Ephemeral Speciation Model Explains Patterns of Diversification Across Time Scales - Erica Bree Rosenblum; Brice A. J. Sarver; Joseph W. Brown; Simone Des Roches; Kayla M. Hardwick; Tyler D. Hether; Jonathan M. Eastman; Matthew W. Pennell; Luke J. Harmon (Evolutionary Biology, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Unravelling contamination signals in biogenic silica oxygen isotope composition: the role of major and trace element geochemistry - Tim S. Brewer; Melanie J. Leng; Anson W. Mackay; Angela L. Lamb; Jonathan J. Tyler; Nicholas G. Marsh (Journal of Quaternary Science, 2008)
The oxygen isotope composition of diatom silica ( δ 18 O diatom ) provides valuable information for palaeoclimate studies where carbonate proxies are either rare or absent in many lakes and ocean sediments. Unfortunately, mineral and rock fragments found alongside diatoms in most sediments can be problematic as the method used will liberate oxygen from all components within the sediment, producing both high‐frequency noise and low‐frequency excursions that can resemble climate signals. Removal of mineral contamination to date has largely relied upon the combination of chemical leaching and physical separation techniques (e.g. sieving, density). This combination can be inefficient and often significant proportions of contaminants are present in the ‘purified’ diatom sample. Using electron optical imaging and whole‐rock geochemistry on previously ‘purified’ diatom samples, a mass balance approach has been developed whereby the types and proportions of residual contaminants are identified. By integrating this information with measured oxygen isotope ratios of the contaminants, it is then possible to remove contamination effects from the δ 18 O diatom record. Contamination effects relating to carbonates, tephra and silt are modelled for cores from Lake Tilo (Ethiopia) and Lake Baikal (Siberia). In both lakes the new modelled δ 18 O diatom curves show less high‐frequency noise, thus enabling better resolution of low‐frequency climate signals. © Natural Environment Research Council (NERC) copyright 2008. Reproduced with the permission of NERC. Published by John Wiley & Sons Ltd.

The effects of organic removal treatment on the integrity of δ18O measurements from biogenic silica - Jonathan J. Tyler; Melanie J. Leng; Hilary J. Sloane (Journal of Paleolimnology, 2007)

Subannual Temporal Variation in Faunal Distributions at the TAG Hydrothermal Mound (26° N, Mid‐Atlantic Ridge) - Jonathan T. P. Copley; Paul A. Tyler; Cindy L. Van Dover; Adam Schultz; Penny Dickson; Sandipa Singh; Margaret Sulanowska (Marine Ecology, 1999)
This paper evaluates the dynamics of two faunal assemblages colonizing high‐ and low‐temperature habitats of the TAG hydrothermal mound on the Mid‐Atlantic Ridge. Timelapse video and photographic transects were used to monitor changes in shrimp and anemone populations from June 1994 to March 1995. During this period, holes were drilled in the vicinity of the target populations by the Ocean Drilling Program (ODP). The a priori expectation of a rapid redistribution of motile alvinocaridid shrimp to occupy the optimal thermal and chemical habitat in response to changes in the pattern of hydrothermal activity was met by the observation of an increase in hydrothermal activity and shrimp population density at the site where a timelapse video system was deployed. The importance of hydrothermal activity as a control on the distribution of vent shrimp is suggested by tidal variations in the distribution of shrimp on a minidiffuser chimney. Sediment deposition during ODP drilling resulted in a temporary disturbance of the shrimp occupying the flat part of the mound surface seen by the timelapse video. In contrast to the changes observed in shrimp distribution, little change was observed in the distribution of anemones across the mound in two photographic transects 10 months apart, with the exception of a localized disturbance where anemones were buried by sediment around an ODP hole. Differences in the response of the shrimp and anemones to changes in the hydrothermal system may result from differences in their motility and rates of biological activity, or reflect a lower trophic position in the case of the shrimp.